New territories, new perspectives the religious impact of the Louisiana Purchase - Callahan, Richard J., 1967- (University of Missouri Press, 2008)
"Marking the first study to take the Louisiana Purchase as the focal point for considering development of American religious history, this collection of essays takes up the religious history of the region including perspectives from New Orleans and the Caribbean and the roots of Pentecostalism and Vodou"--Provided by publisher.